Análise do dimensionamento por software das sapatas de um edifício de múltiplos pavimentos - Giacomassi, Thales Sanches (2021)
This work aims to do a comparative analysis of the shallow foundation's dimensioning in reinforced concrete in a multi-story building using the Eberick software, and also the manual dimensioning in the same shallow foundation to verify the reliability of the program and if it oversizes the structure, causing overspending. At first, all the shallow foundations were dimensioned using the program, introducing the data obtained in the percussion drilling and the structural design's load plant to calculate the permissible soil tension. After that, the shallow foundations were manually dimensioned according to NBR6118:2014, NBR6122:2019, the CEB-70 method. With the data in hand afterward, a comparison was made between all the results. It demonstrated that the dimensioning by the software was totally in favor of safety since it always presented higher values when compared to the other two methods previously mentioned, both in terms of shallow foundation dimensioning and in the area required to support the traction efforts in the shallow foundation's base. Satisfactory results were also achieved about anchoring the pillar bars to the shallow foundations and the anchoring of the shallow foundation's base itself. Therefore, the concrete fully transfers the efforts received. The only unsatisfactory factor of using the software was that the steel area provided a higher value than it was expected.